Breakthrough Pain in Patients with Lung Cancer. A Secondary Analysis of IOPS MS Study - Mercadante, Sebastiano (J Clin Med, 2020)
Aim: To characterize breakthrough cancer pain (BTcP) in patients with lung cancer. Methods: This was a secondary analysis of multicenter study of patients with BTcP. Background pain intensity and opioid dose were recorded. The number of BTcP episodes, their intensity, predictability, onset, duration and interference with daily activities were collected. Opioids used for BTcP, the mean time to meaningful pain relief after taking medication, satisfaction and adverse effects were assessed. Results: 1087 patients with lung cancer were examined. In comparison with other tumors, patients with lung cancer showed: higher background pain intensity (p = 0.006), lower opioid doses (p = 0.005), higher intensity of BTcP (p = 0.005), movement (79.5%) and cough (8.2%), as principal triggers for predictable BTcP (p < 0.009), larger BTcP interference with daily activity (p = 0.0001), higher use of adjuvants (p = 0.0001). No relevant differences in the other parameters examined were found. Conclusion: Patients with lung cancer have their own peculiarities, including higher basal and BTcP pain intensity and the use of more adjuvant drugs for background pain. The most frequent triggers for predictable BTcP are movement and cough. Future studies should be performed to analyze the prevalence of BTcP in patients with different lung cancers as well as the optimal management strategy for background pain and BTcP.